Approach of service evaluation based on trust reasoning for cloud computing - HU Chun-hua1; LUO Xin-xing2; WANG Si-chun1; LIU Yao1 (Tongxin xuebao)
The credibility reasoning and deducing of SC and SP were proposed,which were mainly in the direct trust re-lationship established in interactive process among service entities,the public credibility of the feedback system as a sup-plement.The model used probability density function to represents the credibility of entities based on probability theory,which systematically proposed the reasoning and deducing methods of computing,reasoning and merging based on trust relationship in probability density.Then a new method of correcting QoS of SP entities was provided.Finally,the algo-rithm based on trust reasoning and correcting of QoS service was provided.This model can effectively evaluate the credi-bility of service participants,weakening the influence of unreliable entities in service evaluation and enhancing the quali-ties and accuracy of result in service selection through simulated experiment.